2016
DOI: 10.1177/0734371x16674783
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Development Programs for Executive Directors and Accountability Practices in Nonprofit Organizations

Abstract: Facing the potential leadership deficit and mounting pressures for performance and accountability, government and nonprofit organizations have become more interested in providing training and development programs for their executives. However, existing research falls short in explaining the utility of managerial development programs in achieving performance and accountability in public and nonprofit contexts. This study examines how executives’ participation in various managerial development programs is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Elements of NPOs may facilitate their adjustment by offering more opportunities and encouragement. For example, due to lesser availability of resources, many workers perceive NPOs to offer workers more job autonomy and opportunities for skill development (Lee & Suh, ; Suh, ). Newcomers entering their first full‐time position are expected to be more versatile workers, ready to pitch in on a variety of responsibilities to support the nonprofit's cause (Borzaga & Tortia, ; Dempsey & Sanders, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Elements of NPOs may facilitate their adjustment by offering more opportunities and encouragement. For example, due to lesser availability of resources, many workers perceive NPOs to offer workers more job autonomy and opportunities for skill development (Lee & Suh, ; Suh, ). Newcomers entering their first full‐time position are expected to be more versatile workers, ready to pitch in on a variety of responsibilities to support the nonprofit's cause (Borzaga & Tortia, ; Dempsey & Sanders, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cultural supports in an organization that are conducive to personal growth may be better for nonprofits than the formal type of career development which often requires financial resources. Research has suggested that providing development opportunities for executives is essential not only to themselves but also to their employer (Lee & Suh, ).…”
Section: Job Satisfaction With Rewards and Education–job Matchmentioning
confidence: 99%
“…With the advent of New Public Management (NPM), public sector organizations are adopting private sector human resource management (HRM) practices (Eckerd & Snider, 2017; Podger, 2017). The introduction of broader and multiskilled jobs requires public service organizations to invest billions of dollars annually on training and development programs for their employees (Lee & Suh, 2018; Yang, Wu, Xu, & Chen, 2012). Increased pressure for service quality, operational efficiency, adoption of advanced technologies, and the push to reduce government expenditures amplified the need to assess the effectiveness of employee training programs (Butler & Lobley, 2016; Volet, 2013).…”
Section: Introductionmentioning
confidence: 99%